An Exploratory Study on Inadequacies in Examination System for Visually Impaired Children in Punjab - Muhammad Naveed Khalid, Muhammad Akram Shakir, Farah Shafiq (JIE, 2024)
Dispensing quality of education is constitutional responsibility of every country across the world. Provision of quality education to visually impaired children is a motive endorsed by special education experts in Pakistan. From the previous few decades, the newly created informational technologies have introduced a myriad of assessment tools in the area of Examination system. This paper explores inadequacies in the existing examination system for visually impaired children.